Применение водородного топлива как фактор повышения экологической безопасности - Лесюкова, В. В.; Лапченко, Д. А. (БНТУ, 2021)
The influence of hydrogen as a fuel on improving environmental safety, characteristics of the prospects for its use have been investigated. The conclusion about the relevance of the introduction of hydrogen into the energy system of the Republic of Belarus for the development of a decarbonized economy is made.